Pelatihan Merencanakan Dan Memasang Panel Surya Di Rumah Hunian - Rakhmad Syafutra Lubis; Ramdhan Halid Siregar; Hubbul Walidainy; T. Edisah Putra; Masri (Yayasan Kawanad, 2024)
The community engagement conducted by the lecturers of the Electrical Engineering undergraduate program at the Faculty of Engineering, Syiah Kuala University, aims to enhance the income of young individuals in Kopelma Darussalam, Banda Aceh. Recognizing the need for employment opportunities among youths from lower to middle-income backgrounds, this initiative focuses on providing hands-on skills through training in planning and installing solar panels in residential homes. Consequently, young individuals can become skilled workers in solar panel installation, creating job opportunities, and improving their economic well-being. This training aims to address the increasing demand for renewable energy solutions and the growing interest in solar power adoption among homeowners. Participants will learn about the principles of solar energy, site assessment, system design, installation techniques, and safety procedures. After completing the training, participants are expected to be able to design and install solar panel systems, thereby contributing to the promotion of sustainable energy practices and reducing carbon footprint in residential communities.